2011
DOI: 10.1590/s0102-695x2011005000053
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the acute toxicity of dolabelladienotriol, a potential antiviral from the brown alga Dictyota pfaffii, in BALB/c mice

Abstract: Dolabelladienotriol is a product extracted from the brown marine alga Dictyota pfaffii from Brazil that has been shown to have antiviral activity and low cytotoxicity. Our studies have evaluated the acute toxicity of dolabelladienotriol in BALB/c mice for ten days after administration of a single dose. Among the parameters considered were behavior, weight, biochemical and histological analyses of blood samples taken at three different times (Bs.0, Bs.1 and Bs.2) and optical microscopic examination of organs li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
1
7
0
1
Order By: Relevance
“…The heart showed no changes in the architecture with cardiac fibers very visible to the cut ( Figure 2G, H and I). Finally, we analyze the histological structure of stomach and observed no changes ( Figure 2J, K and L), just as Garrido et al (2011) found in the acute toxicity study of dolabelladienotriol. However in the spleen, as noted in the 1% DMSO group and O. obtusiloba group, was presented an increase of white pulp with a suggestive activation of the germinal center, possibly due to the DMSO solvent used for solubilization of the extract ( Figure 2M, N and O).…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…The heart showed no changes in the architecture with cardiac fibers very visible to the cut ( Figure 2G, H and I). Finally, we analyze the histological structure of stomach and observed no changes ( Figure 2J, K and L), just as Garrido et al (2011) found in the acute toxicity study of dolabelladienotriol. However in the spleen, as noted in the 1% DMSO group and O. obtusiloba group, was presented an increase of white pulp with a suggestive activation of the germinal center, possibly due to the DMSO solvent used for solubilization of the extract ( Figure 2M, N and O).…”
Section: Resultssupporting
confidence: 53%
“…Sasidharan et al (2010) by testing another red seaweed observed no significant signs of toxicity, nor did a single administration of 2000 mg/kg methanol extract of Gracilaria changii cause death during the 14-day observation period. In another acute toxicity work of our group (period of 10 days) with dolabelladienotriol, a natural product derived from brown algae, Dictyota friabilis (as Dictyota pfaffii), all of the animals that received dolabelladienotriol presented a moderate increase in mitosis of hepatocytes and focal areas of hydropic cells in the medulla of the kidneys, even though this study indicates that dolabelladienotriol has low toxicity in administered dose range (Garrido et al, 2011).…”
Section: Resultsmentioning
confidence: 70%
“…Mice deaths were not observed at any dose during the ten-day period. Significant changes were not observed in the concentrations of urea nitrogen, creatinine, alanine aminotransferase, uric acid, and total protein [44]. In 2014, three news dolabellane-type diterpenoids named dolabelladienols A-C were isolated from the brown seaweed Dictyoya pffafi.…”
Section: Brown Seaweeds As a Source Of New Bioactive Prototypesmentioning
confidence: 99%
“…These organisms have traditionally been harvested or cultivated as a food source, such as agar or carrageenan, or for the extraction of secondary metabolites used in the pharmaceutical industry (Marinho-Soriano et al, 2011). In this context, representatives of the genera Laurencia and Dictyota (Lhullier et al, 2010;Domingos et al, 2011;Garrido et al, 2011;Machado et al, 2011;Moura et al, 2011) are target organisms for studies on many different levels of pharmaceutical investigation. Based on a review of the available literature, this paper presents an analysis of the current distribution, together with several aspects of macroalgae diversity, highlighting evidence that identifies how environmental factors related to climate change and the presence of local anthropogenic stressors can affect the ecology and physiology of macroalgae and, consequently, their biotechnological potential.…”
Section: Introductionmentioning
confidence: 99%